Melatonin Protects N2a against Ischemia/Reperfusion Injury through Autophagy Enhancement - 国艳春 王剑飞 王忠强 杨易 王西明 段秋红 (Journal of Huazhong University of Science and Technology. Medical sciences, 2010)
Researches have shown that melatonin is neuroprotectant in ischemia/reperfusion-mediated injury.Although melatonin is known as an effective antioxidant,the mechanism of the protection cannot be explained merely by antioxidation.This study was devoted to explore other existing mechanisms by investigating whether melatonin protects ischemia/reperfusion-injured neurons through elevating autophagy,since autophagy has been frequently suggested to play a crucial role in neuron survival.To find it out,an ischemia/...